Anterior Column Realignment (ACR) in Adult Sagittal Deformity Correction: Technique and Review of the Literature. (April 2016) - Saigal, Rajiv; Mundis, Gregory M.; Eastlack, Robert; Uribe, Juan S.; Phillips, Frank M.; Akbarnia, Behrooz A.
Abstract : Study Design: The anterior column realignment (ACR) procedure was retrospectively reviewed. Objective: To review surgical technique, complication avoidance, case examples, and published results on ACR. Summary of Background Data: For surgical correction of sagittal imbalance, three column osteotomies (3CO) have traditionally been employed for large degrees of correction at a single segment. However, 3CO procedures are technically challenging and carry high morbidity rates. ACR was developed as a less invasive procedure for restoring segmental lordosis. Methods: The ACR surgical technique is reviewed. ACR involves either a lateral, trans-psoas or anterior retroperitoneal approach to sectioning the anterior longitudinal ligament/annulus and placing a hyperlordotic cage. ACR usually also involves a second stage posterior column osteotomy. Three case examples are presented. A review of literature on ACR papers was completed. Results: Twelve papers met inclusion criteria. Ten to 27° of segmental lordosis were reported with use of hyperlordotic cages. 19° increase in mean intradiscal angle was reported when ACR was combined with posterior column osteotomy, 13° more than lateral lumbar interbody fusion alone without a hyperlordotic implant. Reported complication rates ranged from 18 to 47%. The most common minor complications were transient hip flexion weakness (9.3%) and transient paresthesia or dysesthesia (12%). There were few reports of major complications, such as bowel perforation (n = 1) or vascular injury (n = 1). Motor deficit was reported in 11 of 75 cases, lower than reported rates for 3CO. Conclusion: ACR is an emerging, less invasive technique for correction of sagittal deformity ACR has similar restorative capacity as other techniques with same or lower complication rates. Level of Evidence: 4